Political theory and the European constitution - Dobson, Lynn; Føllesdal, Andreas (Routledge/ECPR studies in European political science, 2004)
This timely volume provides one of the first critical assessments of the draft Constitution (released by the Convention on the future of Europe) from the vantage point of political theory.